Validating STEM Pedagogical Content Knowledge Scale for Secondary School Mathematics Teachers (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Science, technology, engineering, and mathematics (known as STEM) field and related jobs are increasinglydemanding, so teachers must be equipped with STEM-based knowledge during classroom instruction in preparing studentswith STEM-relevant skills. However, past studies showed that many teachers were less confident in applying the knowledgethat practically affected students’ interest in STEM opportunities. In this study, researchers intend to measure the validityand reliability of the STEM pedagogical content knowledge instrument (STEMPCK Scale) using the Rasch model analysis.The online survey was distributed to 23 mathematics secondary school teachers' participation. The data was analyzed usingWinsteps version 3.71.0.1 software. The finding showed that all the items are valid, reliable, and compatible to measureSTEM-based knowledge among school teachers. The implications of the research are discussed